Discovery of a novel 2, 3-dimethylimidazo[1, 2-a]pyrazine-6-carboxamide M4 positive allosteric modulator (PAM) chemotype. Issue 3 (1st February 2020) - Temple, Kayla J.; Engers, Julie L.; Long, Madeline F.; Watson, Katherine J.; Chang, Sichen; Luscombe, Vincent B.; Jenkins, Matthew T.; Rodriguez, Alice L.; Niswender, Colleen M.; Bridges, Thomas M.; Conn, P. Jeffrey; Engers, Darren W.; et al.
Graphical abstract: Highlights: Discovery of two novel tricyclic-based M4 PAMs. Utility of scaffold hopping to improve potency/properties/DMPK. Balanced human and rat M4 PAM potency. Rare 8, 9-dimethyl-8 H -pyrazolo[3, 4- h ]quinazoline and 1-methyl-1 H -[1, 2, 3]triazolo[4, 5- h ]quinazoline cores. Abstract: This Letter details our efforts to discover structurally unique M4 PAMs containing 5, 6-heteroaryl ring systems. In an attempt to improve the DMPK profiles of the 2, 3-dimethyl-2H-indazole-5-carboxamide and 1-methyl-1 H -benzo[ d ][1, 2, 3]triazole-6-carboxamide cores, we investigated a plethora of core replacements. This exercise identified a novel 2, 3-dimethylimidazo[1, 2- a ]pyrazine-6-carboxamide core that provided improved M4 PAM activity and CNS penetration.